The discriminative, criterion, and longitudinal validity of small-sided games to assess physical fitness in female basketball players - Gil, E. F.; Rodríguez-Fernández, A.; Vaquera, A.; Suárez-Iglesias, D.; Scanlan, A. T. (Journal of Sports Sciences, 2023)
The validity of small-sided games (SSG) for assessing physical fitness was evaluated in 21 female basketball players from senior (n = 8), under-18 years (n = 6), and under-16 years (n = 7) age categories. Players underwent fitness testing (countermovement jump [CMJ], agility T-test, repeated-sprint ability (RSA) test, and Yo-Yo Intermittent Recovery Test [YYIRT1]) and 3vs3-SSG before and after a 6-week preseason. Player demands were monitored during SSG using local positioning system and heart rate technology. Regarding discriminative validity, senior players produced better CMJ, agility T-test, and YYIRT1 performance (p < 0.05, effect size [ES] = 1.72-2.25), and more distance and PlayerLoad (p < 0.05, ES = 1.53-2.47) during SSG than under-18 players following the preseason. For criterion validity, total distance and distance completing high-intensity decelerations during SSG were significantly (p < 0.05) correlated with CMJ (r = 0.44-0.66), YYIRT1 (r = 0.43-0.63), agility T-test (total distance only, r=-0.51), and RSA test performance (r=-0.49 to -0.52) among all players combined following the preseason. Regarding longitudinal validity, significantly better agility T-test and YYIRT1 performance (p = 0.001, ES = 0.88-0.93) alongside lower heart rate during SSG (p = 0.001, ES = 0.88) were evident for all players combined following the preseason. These results partially support the validity of 3vs3-SSG to assess physical fitness in female basketball players.